(untitled) (Research, Society and Development, 2020)
Environmental education is one of the educational tools used to instigate the human being’s criticality. It must be worked in a comprehensive way in all educational institutions, especially in rural schools due to the particularities of this modality. Therefore, this study had as main objective to evaluate the effectiveness of environmental education actions in the sense of belonging to the subject of the rural school. For that, seven environmental education actions carried out by the Campo Padre Antônio Vieira State School - Elementary School were analyzed through qualitative evaluations. The results of this study made it possible to infer the importance of environmental education in rural schools in environmental, economic and social aspects. Thus, through the valorization of the peasantry’s conceptions and historicity, it was found that environmental education contributed to the development of the sense of belonging to the place where they live. In addition, it was noticed that the actions performed, because they were worked on significantly, translated the students’ conceptions regarding their reality.